Design of an Ergonomic Press Machine Work Aid to Increase Productivity in the Shoe Production Process (Case Study at SMEs One Maxx Mojokerto) - Ardana Isra Rachmadi; Siti Muhimatul Khoiroh (JRSI (Jurnal Rekayasa Sistem dan Industri), 2025)
UKM One Maxx Mojokerto is a small and medium-sized enterprise engaged in shoe production. The production process, particularly in the stage of attaching the upper to the sole, is still carried out manually using basic tools such as hammers, nails, and pliers. This method requires relatively long processing time, high physical effort, and potentially causes ergonomic complaints for workers. This study aims to design an ergonomic press machine as a work aid to improve productivity and operator comfort. The research method includes user needs analysis, anthropometric measurements for tool dimension determination, and work time analysis using the Maynard Operation Sequence Technique (MOST). The results indicate that the ergonomic press machine design is able to reduce production time compared to manual methods, increase work efficiency, and decrease workers’ physical workload. The implementation of this work aid is expected to enhance production capacity while improving ergonomic working conditions for SMEs.